Zanubrutinib (BGB-3111), a Second-Generation Selective Covalent Inhibitor of Bruton’s Tyrosine Kinase and Its Utility in Treating Chronic Lymphocytic Leukemia - Rhodes JM; Mato AR (Dove Medical Press, 2021)
Joanna M Rhodes,1 Anthony R Mato2 1CLL Research and Treatment Center, Northwell Health Cancer Institute, Barbara and Donald Zucker School of Medicine at Northwell/Hofstra, New Hyde Park, NY, USA; 2Chronic Lymphocytic Leukemia Program, Memorial Sloan Kettering Cancer Center, New York, NY, USACorrespondence: Joanna M RhodesCLL Research and Treatment Center, 410 Lakeville Road Suite 212, New Hyde Park, NY, 11042, USATel +1 516 470-4050Fax +1 516 470-4250Email jrhodes3@northwell.eduAbstract: The understanding of the B cell receptor (BCR) pathway and its contribution to chronic lymphocytic leukemia (CLL) pathogenesis have led to the development of targeted BCR inhibitors which have transformed the treatment paradigm of CLL. Ibrutinib is a first-in-class oral Bruton’s tyrosine kinase (BTK) inhibitor which has demonstrated improvements in both progression free (PFS) and overall survival (OS) in both the treatment naïve and relapsed/refractory setting as compared to traditional chemoimmunotherapy. Despite its clinical efficacy, many patients discontinue treatment due to adverse events, which are thought to be mediated through off-target kinase inhibition. Zanubrutinib is a second-generation non-covalent BTK inhibitor with higher potency, allowing for inhibition of BTK with fewer off target effects. Early phase clinical trials have demonstrated excellent efficacy and a well-tolerated safety profile. Long-term follow-up is needed, but zanubrutinib holds promise to be an effective therapy for CLL with a manageable side effect profile and will be an exciting addition to our treatment paradigm.Keywords: chronic lymphocytic leukemia, small lymphocytic lymphoma, BTK inhibitor, zanubrutinib